Pengembangan Dan Implementasi Learning Management System (Lms) Moodle Dengan Pendekatan - Aprila, Dzikri; Nashrulloh, Muhamad Rikza (Jurnal Algoritma, 2025)
The development of computer technology has brought an impact on the advancement of internet technology, including in the field of education. Along with the advancement of the internet, education has also undergone a transformation, one of which is through the use of a learning management system (LMS) such as moodle at the 17 Garut state high school. however, moodle is experiencing interface problems that are confusing for teachers, students, and administrators due to inconsistent displays. This research aims to develop Moodle with a user-centered design (UCD) approach to improve information accessibility, ease of material and task management, and user interest in the application. UCD method is applied through understanding the use, determining user needs, design development, and design evaluation. The results showed that the development of the Moodle interface based on UCD succeeded in increasing ease of use, as evidenced by the results in the system usability scale (sus) test getting an average increase in usability scores from 40 to 68. with this adjustment, the development of the moodle learning management system makes it easier for users to use the LMS.